2012
DOI: 10.1111/j.1469-8137.2012.04161.x
|View full text |Cite
|
Sign up to set email alerts
|

PAP1 transcription factor enhances production of phenylpropanoid and terpenoid scent compounds in rose flowers

Abstract: Summary• Floral scent is a complex trait of biological and applied significance. To evaluate whether scent production originating from diverse metabolic pathways (e.g. phenylpropanoids and isoprenoids) can be affected by transcriptional regulators, Arabidopsis PRODUCTION OF ANTHOCYANIN PIGMENT1 (PAP1) transcription factor was introduced into Rosa hybrida.• Color and scent profiles of PAP1-transgenic and control (b-glucuronidase-expressing) rose flowers and the expression of key genes involved in the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 63 publications
(132 reference statements)
5
113
0
1
Order By: Relevance
“…This argues against metabolic competition but supports the notion that PAP1 has a pleiotropic effect on both pathways (Zvi et al 2006(Zvi et al , 2008. Similarly, 35S:PAP1 transgenic Rosa hybrida showed increased pigmentation as well as eugenol accumulation (Zvi et al 2012). A more general argument against metabolic competition is the temporal separation of the two pathways.…”
Section: Interaction Between Color and Scent At The Biochemical Levelsupporting
confidence: 58%
See 1 more Smart Citation
“…This argues against metabolic competition but supports the notion that PAP1 has a pleiotropic effect on both pathways (Zvi et al 2006(Zvi et al , 2008. Similarly, 35S:PAP1 transgenic Rosa hybrida showed increased pigmentation as well as eugenol accumulation (Zvi et al 2012). A more general argument against metabolic competition is the temporal separation of the two pathways.…”
Section: Interaction Between Color and Scent At The Biochemical Levelsupporting
confidence: 58%
“…Bats, bees, butterflies, hummingbirds, and moths are able to sense floral scents and have been shown to discriminate among odor differences (von Helversen et al 2000;Kunze and Gumbert 2001;Wright et al 2002Wright et al , 2005Ô mura and Honda 2005;Kessler et al 2008;Zvi et al 2012). Recently, it was shown that the hawkmoth Manduca sexta processes olfactory stimuli through two olfactory channels, allowing it to coordinate an innate preference with olfactory learning (Riffell et al 2012).…”
Section: Floral Scent Floral Volatiles Act As Species-specific Longdimentioning
confidence: 99%
“…Recently, MYB factor Ph MYB4, which suppresses production of p-coumaric acid-derived volatiles, such as eugenol and isoeugenol, through downregulation of genes encoding upstream cinnamate 4-hydroxylase, was identified (Colquhoun et al, 2011a). EMISSION OF BENZENOIDS II (EOBII), similar to PAP1 and in contrast with ODO1, has been shown to regulate the transcription of both shikimate pathway genes and genes directly involved in the biosynthesis of phenylpropanoid volatiles (Verdonk et al, 2005;Dare et al, 2008;Ben Zvi et al, 2008;Spitzer-Rimon et al, 2010;Zvi et al, 2012). While it has been recently suggested that EOBII may also have activities outside the scope of floral scent production (Colquhoun et al, 2011b), the epistatic relations between EOBII and ODO1 have been confirmed: EOBII binds directly to ODO1's upstream regulatory sequence and transcriptionally activates its expression (Van Moerkercke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Petunia hybrida flowers, benzenoid scent production has been shown to be transcriptionally controlled through the ODORANT1 R2R3 MYB TF targeting the 5-enol-pyruvylshikimate-3-phosphate synthase promoter (Verdonk et al, 2005). Transgenic roses (Rosa hybrida) that overexpressed the PRODUCTION OF ANTHOCYANIN PIGMENT1 R2R3 MYB TF produced 6.5-fold higher concentrations of terpenoids than control flowers, which was partly explained by up-regulation of a GERMACRENE D SYNTHASE gene, although no direct evidence of promoter interaction was presented (Zvi et al, 2012). In cotton (Gossypium hirsutum), the action of a WRKY TF regulates the sesquiterpene synthase gene (+)-d-CADINENE SYNTHASE-A involved in gossypol production (Xu et al, 2004), whereas in Arabidopsis inflorescences, the basic helix-loop-helix MYC2 directly binds and activates the promoter of the sesquiterpene synthase gene TPS21, inducing sesquiterpene release (Hong et al, 2012).…”
mentioning
confidence: 99%